EVALUASI KEBIJAKAN PROGRAM BANTUAN PANGAN NON TUNAI (BPNT) DALAM PENANGGULANGAN KEMISKINAN DI KABUPATEN MOJOKERTO - Dwita Agustina; Suci Megawati (Universitas Negeri Surabaya, 2022)
Poverty is a strategic issue experienced by all countries in the world, including Indonesia. given the importance of proper analysis in poverty alleviation, the government's role is very necessary. One of the efforts made by the government is the establishment of the Non-Cash Food Program (BPNT). The BPNT program is a program of providing food assistance in the form of non-cash from the government which is given to KPM every month through a banking mechanism. This program has been implemented in all regions of Indonesia, including in Mojokerto Regency. The purpose of this study is to determine how much the quality of expenditure (output) and the impact given, and to find out whether there are deviations in its application. The type of research used is descriptive with a qualitative approach. The data collection techniques in this study were in the form of literature study, observation, interviews, and questionnaires. Sources of data used are primary and secondary sources. While the focus of this research is based on the policy evaluation criteria according to Bridgman and Davis (2000:130) which include: Inputs, Processes, Outputs, and Outcomes. Data analysis used interactive model according to Miles and Huberman (1992:16). Based on the results of the study, the BPNT Program in Mojokerto Regency greatly helped KPM ease their daily expenses, so that KPM's income could be used to meet other needs. Thus, the BPNT Program in Mojokerto Regency can be said to be successful, judging from the level of conformity between the plan and realization. However, there are still shortcomings in the mechanism for distributing aid, it is hoped that in the future the implementation of the BPNT program in Mojokerto Regency can switch from the package system and can run the mechanism for distributing aid in accordance with the applicable general guidelines. Keywords: Non-Cash Food Assistance Program (BPNT), Evaluation, Public Policy